2016
DOI: 10.1007/s12593-012-0067-x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Eaton-Littler’s Reconstruction for Traumatic Dislocation of the Carpometacarpal Joint of the Thumb—A Case Report and Review of Literature

Abstract: Isolated traumatic dislocation of the carpometacarpal joint of the thumb is an uncommon injury. Left untreated, resulting mechanical instability of this joint interferes with normal function of the hand and can lead to articular degeneration of the joint. Most are amenable to closed reduction with or without supplementary pinning. We present a case of a 21 year old female patient with continual instability of the carpometacarpal joint of her right thumb, following closed reduction and pinning. Surgical stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
(44 reference statements)
0
12
0
1
Order By: Relevance
“…Most of the previous case reports and case series suggested an attempt at a closed reduction of this joint as the first line of management 4–16. If the joint was stable post-reduction, the joint could be immobilised in a thumb spica cast or splint for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous case reports and case series suggested an attempt at a closed reduction of this joint as the first line of management 4–16. If the joint was stable post-reduction, the joint could be immobilised in a thumb spica cast or splint for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The method of ligament reconstruction used by Simonian and Trumble was the technique described by Eaton, in which a portion of the flexor carpi radialis tendon, with its insertion on the second metacarpal preserved, was re-routed through a drill hole in the base of the first metacarpal from palmar to dorsal, passed deep to the abductor pollicis longus insertion, then passed around the remaining flexor carpi radialis and secured over the radial side of the joint 12. Jeong et al also reported success with this technique, while Iyengar et al achieved success with a slight modification to the technique 13 17. Annappa et al used a variation of this technique together with K-wire fixation for additional stabilisation of the first carpometacarpal joint 6…”
Section: Discussionmentioning
confidence: 99%
“…To our experience, radiographic assessment of CMCJ I instability under dynamic conditions seems probably to be the method of choice (Case Presentation 4). For treatment of CMCJ I dislocation injuries it is still controversial whether CRPP is or is not superior over open reduction with ligament reconstruction and pinning (ORLRP), but it must be noted that CRPP can be associated with persistent instability in up to 2/3 of patients [32,34,35,39,41,[44][45][46][47]. However, in order to avoid post-traumatic OA the creation of a stable and correct aligned CMCJ I utilizing varying surgical treatment options is without alternative.…”
Section: Carpometacarpal Joint I (Thumb)mentioning
confidence: 99%
“…Where there is no evidence of osteoarthritis, a volar beak ligament reconstruction using the modified Eaton–Littler’s technique as described by Iyengar et al. (2013) is performed, along with capsular tightening using a Silfverskiöld technique.…”
mentioning
confidence: 99%